PENGARUH FINANCIAL DISTRESS, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM SERTA DAMPAKNYA PADA NILAI PERUSAHAAN (PT WASKITA KARYA 2013-2023) - M Abiyyu Shaula Ardan Ardan (Accounting Journal of Ibrahimy (AJI), 2024)
Overall, the main target in this study is to examine the effect of variables such as financial distress, capital structure, and company size on stock prices and their impact on the value of PT Waskita Karya Tbk. 2013-2023. Quantitative method will be the method that will be used in this study by collecting a sample of quarterly financial statements for the period 2013 to 2023. The independent variables include financial distress, capital structure, and firm size, while the dependent variables are stock price and firm value. This research will use a sample of 40 quarterly financial statements selected through purposive sampling technique. From the results of research on 40 samples of quarterly financial statements, it can be concluded that multiple regression analysis is the method of analysis to be used. The following results have been obtained: (1) Financial Distress has a significant positive effect on Stock Price. (2) Capital Structure has a significant negative effect on Stock Price. (3) Company Size has a significant positive effect on Stock Price. (4) Financial Distress has a significant positive impact on Firm Value. (5) Capital Structure has a significant positive impact on Firm Value. (6) Company Size has no impact on Company Value.